INCREASING ABILITY READING THE UNDERSTANDING OF STUDENTS IN CLASS V SD KRANJINGAN 05 JEMBER THROUGH COOPERATIVE MODEL TYPE TPS - Muhammad Aqil; Fadly A Karim (Jurnal Dikdas, 2020)
Based on preliminary observations carried out by researchers at SD Kranjingan 05 Jember, it shows that the learning process of reading is still done individually. Weaknesses in individual learning, can be overcome by using a type of cooperative learning model. Improving the process and reading comprehension results are the main objectives of this research. The process of reading comprehension includes aspects of planning and implementation. While reading comprehension results, refer to the evaluation of learning. The method used in this study is the classroom action research method. The target in this research is fifth grade elementary school students. Kranjingan 05 Jember, which is divided into 15 couples. The study was conducted in two cycles. The results of the study using the type of TPS cooperative learning model showed that students' reading comprehension skills improved with the acquisition of test scores obtained by students in each group in the first cycle 69.6% and the second cycle 80.8%. This shows that in the second cycle the test score increased and had reached the target of the KKM of 75%.